Mengkaji Faktor dan Kesan Pendedahan Pornografi dalam Kalangan Pelajar Sekolah di Perlis yang Mengikuti Program Intervensi Tentang Bahaya Pornografi - Azrul Nizah bt. Yussof; Siti Nur Thazliah bt. Mohd Thazali; Surizan b. Romli (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Malaysia boasts the highest number of IP addresses dedicated to uploading and downloading child pornography in Southeast Asia, as highlighted by Assistant Commissioner Ong Chin Lan during the "Cyber Protection for Children" seminar in 2018. This revelation spurred researchers to deliver intervention lectures on the perils of pornography across various schools in Perlis. In total, 1191 questionnaires were dispersed among students to explore the factors and impacts of their exposure to pornography and gauge their response to the lectures. Analysis of the questionnaire data using SPSS 2.2 software revealed that 80.6% of students were engaged with pornography, with 43.6% accessing it via the internet/pop-ups, 24.5% through television/movies, and the remainder from magazines/anime and smartphone applications. Most students admitted to consuming pornographic material alone, attributing their behavior to curiosity and arousal. Consequently, researchers emphasize the importance of proactive parental monitoring and advocate for schools to collaborate with relevant stakeholders in organizing additional intervention programs. Such initiatives aim to mitigate students' exposure to pornography and counteract its adverse effects effectively.